Partnering for Change: collaborating to transform occupational therapy services that support inclusive education - Wenonah Campbell; Wenonah Campbell; Cheryl Missiuna; Cheryl Missiuna; Leah Dix; Sandra Sahagian Whalen (Frontiers Media S.A., 2023)
The United Nations champions inclusive education as a moral obligation, requiring equitable learning environments that meet all individuals' diverse learning needs and abilities, including children and youth. Yet the practice of inclusive education is variable and implementation challenges persist. A participatory action research framework was used to develop a solution, Partnering for Change (P4C), which is a tiered service delivery model that bridges health and education by re-envisioning occupational therapy services and transforming the role of the occupational therapist from a service provider for individual children to a collaborative partner supporting the whole school community. This perspective article will describe the P4C model and its evolution, and will outline how it has been implemented in Canadian and international contexts to facilitate children's inclusion and participation in educational settings.